Striving for Equity Healthcare in Sri Lanka from Independence to the Millennium, 1948-2000 - Jones, Margaret (New Perspectives in South Asian History, 2020)
Focusing on the period from independence in 1948 to the millennium this book is an historical analysis of the process by which Sri Lanka became a model of how a nation with limited resources could nevertheless achieve health indicators on a par with the developed world through the development of a primary healthcare system. In so doing it had to interact and negotiate with global health actors such as the World Health Organization while maintaining its own agency. Based on a close reading of original archival sources it is an in-depth exploration of these questions viewed through a series of case studies which highlight both the successes which contributed to this outcome and the inadequacies of those efforts when seen at the micro level. A primary health care infrastructure is an essential prerequisite for the delivery of preventive health care; how this was developed and delivered to the entire population forms the first substantive chapter. Since the incidence of tuberculosis in a community serves as a marker of a country's achievement in meeting basic needs and establishing social justice there follows an examination of policies to control TB. The most vulnerable group in a nation are its children and they are also the source of a nation's future human capital. Two chapters discuss children's health; firstly the problem of childhood malnutrition and secondly the implementation of the successful immunization programme. Demographic change means a double disease burden of non-communicable diseases alongside communicable diseases and how this considerable challenge is met is the subject of the last chapter. Furthermore these topics enable a discussion of the significance and problems of an international policy transfer to less well-resourced environments.